A Novel Use of a Novel Drug: Preoperative Nasal Preparation with Dexmedetomidine for Transnasal Transsphenoidal Neurosurgery Approach in Skull Base Neurosurgery - Hrishi, Ajay Prasad; Lionel, Karen Ruby; Nair, Prakash (Indian Journal of Neurosurgery, 2017)
Introduction Transnasal transsphenoidal (TNTS) approach is preferred for surgical excision of the pituitary gland. Despite its numerous merits, the TNTS approach creates wide fluctuations in hemodynamic parameters that are attributed to the routine application of adrenaline-soaked nasal packing and the intense noxious stimulus during the surgery.Aims To evaluate the effect of dexmedetomidine for preoperative nasal passage preparation on the surgical field visualization and hemodynamic profile of patients during TNTS surgery.Material and Methods Cotton strips soaked in dexmedetomidine were used for nasal preparation. The primary outcomes studied were the quality of surgical field visualization through the endoscope and the amount of bleeding that occurred while raising the nasal mucosal flap. The secondary outcomes assessed were the intraoperative anesthetic and analgesic requirement and the hemodynamic profile.Statistical Analysis Data from the study were summarized as mean and SD. Associations were tested using chi-square test for nonparametric data and for continuous variables ANOVA for repeated measures. A p-value < 0.05 was considered as statistically significant and < 0.01 as highly significant. SPSS 17.0 was used for analysis.Results Seventeen (85%) patients had a Formmer's score of 1, which was an excellent surgical field quality. Two (10%) patients had a Formmer's score of 2, and one (5%) had a Formmer's score of 3. There were no statistically significant variations in heart rate and blood pressure with reduced anesthetic requirement.Conclusion Intranasal dexmedetomidine provides good surgical field conditions with the added advantage of lesser hemodynamic fluctuations.
Keywords: intranasal dexmedetomidine; transnasal trans-sphenoidal; skull base neurosurgery